Simulation of wire and arc additive manufacturing of 308L stainless steel with coldarc gas metal arc welding - Mohd Jmmani, Nur Aisyah Nabilah (2021)
This objective is to study the effect of parameters on coldArc GMAW of 304L stainless steel plate using 1.2 mm diameter of 308L stainless steel welding wire. A Taguchi response of Design of Experiments (DOE) using Minitab software with 9 experiments following the Taguchi L9 Orthogonal Array Design was performed to optimize the output response of simulation data for length, width, and depth of weld bead dimension from MATLAB of Smart Weld Rosenthal’s Steady-State 3D Isotherms. The simulation was conducted using input power (current and voltage) and welding speed with low, medium, and high which include 70 A, 75 A, and 78 A (arc current), 15 V, 16 V, and 17 V (voltage), 400 mm/min, 600 mm/min, and 800 mm/min (welding traveling speed). Based on the Taguchi analysis predicted the best result from the simulation work for weld bead dimensions (height and width) and depth of penetration would be obtained when the optimized values for weld parameters was 75 A, 16 V, and 800 mm/min. The most significant parameters to deposit stainless steel with coldArc GMAW were welding travel speed followed by arc current and voltage. These factors are critical in controlling the weld height, width, and depth of penetration, whereby high heat input affects mechanical and microstructure changes and decreases the weld efficiency of the finished product and create energy loss.